Influence of long-fibre content on the reinforcement capacity of nonwovens obtained from recycled textile waste for application in cement composites - Bárbara Julián; Josep Claramunt; Mònica Ardanuy; Heura Ventura (Case Studies in Construction Materials, 2025)
The use of nonwoven fabrics made from recycled textile fibers as reinforcement for cement-based composites offers a synergistic solution for the textile industry and the building sector, both known for their significant environmental impacts. However, a primary limitation in the reinforcing capacity of these nonwovens is the short length of recycled fibers. To overcome this, incorporating longer virgin fibers becomes necessary, which can reduce the material's overall sustainability. Therefore, it is crucial to determine the optimal composition of nonwoven fabrics in terms of recycled short and virgin long fiber content to develop cement building materials with a strong balance of mechanical performance and sustainability. This study investigates the effect of long fiber content on the mechanical behavior of nonwovens prepared from recycled fibers, incorporating long fibers ranging from 0 % to 40 %. Nonwoven fabrics were produced using an enhanced carding and needle-punching method and subsequently characterized for their mechanical properties. Cement composite plates prepared with these nonwovens were then tested under bending and tensile forces to assess their performance. Composites reinforced with nonwovens containing 30 % and 40 % long fibers exhibited excellent flexural and tensile strength (>19 MPa and ∼4 MPa, representing increases of 37 % and 46 %, respectively) and a toughness increase exceeding 160 % compared to composites without long fibers. Digital Image Correlation (DIC) revealed more uniform crack distribution at higher long fiber content. A composition with 30 % long fibers (C30) emerged as the most suitable, offering an optimal balance between mechanical performance and a high recycled fiber content.